Eustatic versus tectonic control in an intraplate rift basin (Leza Fm, Cameros Basin). Chronostratigraphic and paleogeographic implications for the Aptian of Iberia - Suarez-Gonzalez, P.; Quijada, I. E.; Benito, M. I.; Mas, R. (Journal of Iberian Geology, 2013)
The Leza Formation is a carbonate unit of the northern Cameros Basin (N Spain) with controversial age, stratigraphic position, and sedimentological interpretation. It was deposited in a series of fault-bounded tectonic depressions along the northern margin of the basin. The Leza Fm overlies and changes laterally to the siliciclastic Jubera Fm, and the thickness of both units is also controlled by faults. Although the Leza Fm has been traditionally interpreted as lacustrine with sporadic marine incursions, detailed sedimentological analysis reveals new and very abundant evidences of marine influence: sedimentary structures of tidal origin, common marine fossils (dasycladales and foraminifers), and homogeneous populations of porocharacean charophytes, indicative of brackish conditions. Thus, this unit is interpreted as deposited in a system of coastal-wetlands with both fresh-water and sea-water influence, laterally related with the alluvial deposits of the Jubera Fm and the fluvio-lacustrine deposits of the Enciso Gr towards the centre of the basin. Using the chronostratigraphic ranges of the marine fossils and the lateral relationship with adjacent units, the Leza Fm is confirmed as part of a depositional sequence late Barremian - early Aptian in age. Furthermore, a transgressive trend is defined in the Leza Fm, which is compared with the eustatic evolution of the neighbouring Basque-Cantabrian, Iberian and Pyrenean marine basins, allowing correlation of the upper part of this unit with the widespread eustatic maximum of the middle-upper part of the early Aptian. This eustatic influence provided additional accommodation space to that created by tectonics. These data from the Cameros Basin are contrasted with a thorough compilation of paleogeographic data, showing that, during the early Aptian transgression, marine influence was likely to reach the northern Cameros Basin, not only coming from the SE Iberian Basin, as previously interpreted, but also from the NW Basque-Cantabrian Basin. This resulted in a probable link between Boreal and Tethyan marine realms